Hubungan Antara Self Efficacy dengan Pengambilan Keputusan Karier pada Siswa Kelas XII Putri MA Miftahul Qulub Galis Pamekasan - Nuri Istiqlailia; Ishlakhatus Sa'idah (Institut Agama Islam Neegri Madura, 2021)
This research was motivated by many students at MA Miftahul Qulub who still lacked confidence in making career decisions. This can be seen from their inability to determine further studies to college as desired. There are also some students who are still confused about what to do after graduation. Self efficacy can influence students in determining the chosen decision making. So that in this study, researchers are interested in conducting research with the title